Sistem Informasi Geografis Untuk Pemetaan dan Pencarian Rumah Sakit di Kota Baturaja - Nanda, Risvi Claresta; Vallentino, Anugrah; Putra, Dimas Anggara; Pujianto, Pujianto (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to develop an integrated database-based geographic information system (GIS) that can accurately present information on the locations of hospitals in Baturaja City and make it easily accessible to the public. The research methods used include collecting hospital location data through observation and documentation, followed by the design and development of a GIS system that integrates spatial data and attribute data in the form of digital maps. The system was developed to display the distribution of hospitals and support the process of searching for the nearest location. The results of the study show that the geographic information system that was developed is capable of displaying hospital location information visually and informatively, making it easier for users to find the hospital they need. In addition, this system can also be used by the health department as a supporting tool in managing hospital distribution data and urban spatial planning.